The Perception of Marketing Communication with the Evening Dress Hire Shop in Bangkok - โขงรัมย์ พธิดา (Journal of Humanities and Social Sciences, Rajapruk University, 2020)
The aims of this study were to: 1) study lifestyle patterns of consumer using the services of evening dress hire shop, 2) study marketing communication toward customer perception of evening dress hire shop, 3) compare marketing communications toward customer perception based on personal characteristics of evening dress renters, and 4) study relationships between lifestyle patterns and marketing communication toward customer perception of evening dress hire shop. Data were collected by questionnaires in sampling of 408 respondents living in Bangkok. The sample was chosen randomly and incidentally. Statistics used for data analysis were frequency, percentage, mean, standard deviation of data, t-test, One-way ANOVA) and Pearson product moment correlation. The results show that the overall score lifestyle patterns of consumers using the service of evening dress hire shop are at a moderate level. The customer’s perception on marketing communication on evening dress hire shop is at a moderate level score. Comparing perceptions of marketing communication based on personality traits including the different existence of gender, education age and income results in different perception of marketing communication at the statistical level of .05. There is no different perception of marketing communication for different occupations. Moreover, lifestyle patterns of consumer are moderate positively related to perception of marketing communication at the statistical level of .05.